Metabolomic Profile Differences Between Demented and Non-Demented APOE4 Carriers in the Long Life Family Study. (17th December 2021) - Jain, Mohit; Murabito, Joanne; Zmuda, Joseph; Christensen, Kaare; Province, Michael; Jin, Zhezhen; Lee, Joseph; Yao, Yujing
Abstract: The apolipoprotein ε4 (APOE4) is the most prevalent genetic risk factor for late-onset Alzheimer's Disease (AD). Here we assessed the metabolomic profile differences between APOE4 carriers who develop AD vs. who do not in a sample of 142 participants, aged 65-99 years in the Long Life Family Study (LLFS). Of 7, 321 metabolites, we applied a generalized estimating equation model and identified 137 metabolites significantly associated with AD. Subsequent multivariate analyses were performed for prediction and clustering recognition. Among annotated metabolites, 8 metabolites in the eicosanoids and docosanoids group, 3 metabolites in the fatty acids group, and arabitol were associated with elevated risks of AD (OR: 1.6-2.3). On the other hand, a different set of metabolites were associated with reduced risks of AD (OR: 0.34-0.64). These metabolomic profile differences can be used to help with early diagnosis in the population of older APOE4 carriers in the pre-clinical stage.